Med besedo in besedno zvezo - Stramljič Breznik, Irena (2018)
Between the Word and the Word Phrase. The title Between the Word and the Word Phrase highlights the lexicological focus of the monograph, embracing both the field of word formation and the field of phraseology and examining them through a corpus-based analysis. The relationship between the word and the word phrase is emphasized in the two basic chapters, which are connected through a third dimension – the interpretative approach based on linguistic culturology. This approach highlights the culturally-oriented perception of the world by a linguistic community as it is reflected through language. The monograph explores these topics in the lexicological chapter, which combines ethnological, semantic and phraseological data from the Gigafida general corpus and the TURK specialized corpus, to examine lexical units such as kaša (‘porridge’), kokoš (‘chicken’), voda (‘water’), odlika (‘virtue’) and odličnost (‘excellence’). In addition to this, it includes an analysis of word formation based on a cognitive linguistic approach, which is new in Slovene word formation. Considering the morphemic and overall formational flexibility of the Slovene language, the cognitive approach offers many new possibilities for the interpretation of complex words as symbols created through the association of the phonological and semantic structure.
Keywords: lexicology; word formation; phraseology; corpus linguistics; cognitive grammar; linguistic culturology